Implementasi Strategi Diferensiasi dalam Pembelajaran Bahasa Arab pada Kurikulum Integratif di SMP Islam Madinatul Ilmi Legoso - Balkist, Vhebe Angela; Humairah, Siti; Tuniam, Naila; Maswani (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2026)
This study aims to analyze the differentiated instructional strategies in Arabic language learning based on the curriculum implemented at Madinatul Ilmi Islamic Junior High School. Using a descriptive qualitative approach and a case study method, data were collected through in-depth interviews, classroom observations, and documentation. The findings reveal that teachers apply differentiated strategies in three main aspects: content, process, and product. Instructional materials are adjusted according to students’ initial abilities through tiered textbooks, ranging from Kitabati to Al-‘Arabiyyah Bayna Yadayk. The learning process is designed to be flexible, employing affective and gradual approaches, while assessments are conducted formatively through tiered tasks that reflect individual student progress. Furthermore, instruction is contextualized with daily Islamic practices, such as prayer and worship, to strengthen students' understanding of religious meaning in language use. These findings offer an adaptive Arabic language learning model that responds to student heterogeneity and integrates Islamic values in an applicable way, contributing a novel perspective to the development of faith-based differentiated instruction strategies in Islamic schools